Gambling on Genes: Ambiguity Aversion Explains Investment in Sisters' Children - GUHA, Brishti (Institutional Knowledge at Singapore Management University, 2012)
Many men invest in their sisters’ children instead of their wives’. Existing theories addressing such behavior depend on the level of paternity probability in such men’s societies being implausibly low. I link this anthropologically observed investment behavior with the experimentally observed phenomenon that some individuals are ambiguity averse. Arguing that men’s decisions are made under ambiguity, I show that an increase in ambiguity aversion results in investment in sisters’, rather than wives’, children. I show that this can happen even under risk neutrality. I also consider the special cases of a SEU maximizer and of extreme ambiguity aversion in the Gilboa-Schmeidler sense. Extremely ambiguity averse individuals invest in sister’s children regardless of risk preference or actual paternity rates. An increase in ambiguity, rather than an increase in ambiguity aversion, in contrast, may affect the investment decision either way. When sufficiently many men are ambiguity averse, inheritance norms could become avuncular, affecting women’s incentives and generating a bias towards actual nonpaternity. This is consistent with, but represents an unusual explanation of, data which show correlations between inheritance norms and actual paternity rates.